Medical device design for adolescent adherence and developmental goals: a case study of a cystic fibrosis physiotherapy device - Lang, Alexandra. R.; Martin, Jennifer L.; Sharples, Sarah; Crowe, John A. (Dove Medical Press, 2014)
Purpose: This study investigates the psychosocial aspects of adolescent medical device use and the impact on adolescent adherence and goals for the transitional years between child and adulthood.